Therapeutic Angiogenesis Using Basic Fibroblast Growth Factor in Combination with a Collagen Matrix in Chronic Hindlimb Ischemia - Jianyin Zhou; Yilin Zhao; Jinling Wang; Sheng Zhang; Zhengjin Liu; Maochuan Zhen; Yun Liu; Pingguo Liu; Zhenyu Yin; Xiaomin Wang (The Scientific World Journal)
Although therapeutic angiogenesis by angiogenic cytokines is a feasible strategy to improve regional blood flow in ischemic regions, the optimal delivery mode needs to be established. Here we designed a complex of collagen matrix (CM) and basic fibroblast growth factor (bFGF) and evaluated its proangiogenic effect in ischemic hindlimbs. The bFGF-CM was prepared using lyophilization. The morphology, porosity and toxicity of CM were examined. The bFGF releasing profile and bioactivity of released bFGF were assessed. bFGF-CM was intramuscularly implanted into the rabbit ischemic hindlimb model. Oxygen saturation parameters (OSP) of ischemic hindlimbs was measured to evaluate the extremity perfusion at intervals. Histological examination was performed to evaluate the level of angiogenesis. The CM and bFGF-CM were of identical multiporous structure lacking cytotoxicity. The releasing profile lasted 10 days and the released bFGF remained bioactive. OSP in bFGF-CM group was significantly higher than that in CM, bFGF and ischemic groups at 2 and 4 weeks. The number of capillaries and mature vessels in bFGF-CM group were significantly greater than that in untreated control, CM and bFGF groups. Therefore, bFGF-CM enables the safe and effective long-term release of bFGF with improved angiogenesis in ischemic hindlimbs compared with CM devoid of bFGF.